Evolution of lipid classes and fatty acid digestibility along the gastrointestinal tract of broiler chickens fed different fat sources at different ages. (10th October 2018) - Rodriguez-Sanchez, R; Tres, A; Sala, R; Guardiola, F; Barroeta, A C
ABSTRACT: The aim of the present study is to evaluate the effect of the dietary fat saturation degree and age on the lipid class (TAG, DAG, MAG, and FFA) composition and fatty acid digestibility along the gastrointestinal tract (GIT ) and excreta in broiler chickens. A total of 120 one-day-old female broiler chickens were randomly distributed in 2 dietary treatments (6 cages/treatment), which resulted from the supplementation of a basal diet with 6% of soybean oil or palm oil. Two digestibility balances were carried out at 14 and 35 d and fatty acid digestibility and lipid class composition were determined in the gizzard, duodenum, jejunum, ileum, and excreta. Along de GIT, both fatty acid digestibility and lipid class composition were influenced by the dietary fat source and the age of the chickens. The absorption of the unsaturated fat was more efficient and faster than it was for the saturated fat. The ability of adult chickens to absorb fat was higher than for young chickens. The results show that the duodenum is the main place of fat digestion (hydrolysis), and the jejunum the main place of fat absorption. The role of the ileum on fat absorption is very important, as it is the last segment of the GIT where the absorption of fatty acids has been described. Thus, it was the contribution of the ileum that was responsible for the higher fat utilization observed for animals fed the unsaturated diet than for those fed the saturated diet at 14 d, and it was also responsible for the improvement on the utilization of the saturated diet between 14 and 35 d. All the results suggest that the absorption of fatty acids is more limiting than is hydrolysis, because the main differences were observed in the jejunum and ileum, where the absorption of fatty acids takes place.